THE INFLUENCE OF WORK EXPERIENCE, COMPETENCE, WORK ENVIRONMENT ON WORK EFFECTIVENESS WITH WORK MOTIVATION AS A VARIABLE INTERVENING AT THE OFFICE OF THE PORT MASTER AND CLASS II PORT - Deddy Surachmad; Bambang Satriawan; Muammar Khaddafi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study examines the Influence of Work Experience, Competence, Work Environment on Work Effectiveness with Work Motivation as an Intervening Variable at the Harbormaster and Port Authority Office of Class II Teluk Bayur. This study uses quantitative research. The data analysis technique in this study uses Partial Least Square (PLS) which is a Multivariate Analysis in the second generation using structural equation modeling (Structural Equation Model/SEM). Work Experience has a significant influence on the Work Motivation variable. Competence has a significant influence on the Work Motivation variable. Work Environment has a significant influence on the Work Motivation variable. Work Motivation does not have a significant influence on the Work Effectiveness variable. Work Experience has a significant influence on the Work Effectiveness variable. Competence has a significant influence on the Work Effectiveness variable. Work Environment has a significant influence on the Work Effectiveness variable. Work Motivation has a positive and significant influence in mediating Work Experience on Work Effectiveness. Work Motivation has a positive and significant influence in mediating Competence on Work Effectiveness. Work Motivation has a positive and significant influence in mediating Work Environment on Work Effectiveness.